Project Based Learning Model in Teaching Deutsch Fűr Tourismus for Foreign Language Students - Muhammad Anwar; Yusri Yusri; Femmy Angreany; Arlian Fachrul Syaputra; Hasmawati Hasmawati (Journal of Educational Science and Technology (EST), 2020)
This study aims to determine the effectiveness of the application of PBL (Project Based Learning) learning models in Deutsch für Tourismus courses in foreign language majors. This research is an experimental study using one group design as an experimental group without involving the control group. Respondents in this study were 30 students who were programming the Deutsch fuer Tourismus course. Student speaking skills data were measured using assessment rubrics with intervals of 1 to 9. This assessment rubric was adapted from assessments in the IELTS test specifically in aspects of speaking skills. The intervention given was in the form of implementing the PBL model for 6 meetings, where each meeting was 2 hours long. Data analysis techniques used are descriptive statistics and inferential statistics. There are 4 types of advantages of the PBL model that are felt by students when implemented in the learning process namely 1) can trigger students to find and explore ideas or ideas that they want to express when speaking. 2) train students to work in groups to solve a problem. 3) This model produces products that are self-developed by students. 4) The PBL model requires students to read a lot, so that it can have a positive effect in increasing student reading interest. Keywords: Learning Model; Project Based Learning; Deutsch für Tourismus; Speaking Skills